Psychologiczne aspekty pracy z uczniem z doświadczeniem migracyjnym - Szydłowska, Paulina; Durlik, Joanna (Postscriptum Polonistyczne, 2020)
The article summarises the most important issues concerning working with students with migration experiences: foreign teenagers and children, young refugees and children of repatriated persons. The article authors underline the psychological aspects and not only refer to changes in school curricula or language differences, but also discuss the cultural differences and issues such as cultural shock (experienced also by people who come back to the country of their origin), adaptive stress or post-traumatic stress. The authors also highlight the unique abilities of the migrant students and suggest effective ways of using them in school education. The article concludes with a short presentation of the legal acts that define they ways of supporting this group of students and with a list of publications that may become a source of inspiration for anyone interested in the matter.